Heat-conducting wear-resistant organic silicon composite resin and preparation method thereof

By using modified boron nitride nanosheets, MoS2@NiPS hybrids and coupling agents to modify silicon dioxide and other fillers in silicone resins, and applying batch pulse electric fields, the problem of insufficient thermal conductivity and wear resistance of traditional silicone resins is solved, and the efficient thermal conductivity and wear resistance are improved.

CN119912815AActive Publication Date: 2025-05-02HARBIN ENG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510420964.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-05-02
Estimated Expiration
2045-04-07

AI Technical Summary

Technical Problem

Traditional silicone resins have shortcomings in thermal conductivity and wear resistance, which are difficult to meet the needs of fast and efficient heat dissipation in high heat flow density scenarios, and are prone to wear problems during friction.

Method used

The double modified boron nitride nanosheets, MoS2@NiPS hybrids and coupling agent modified silica are used to improve the compatibility and interface strength of the filler and the matrix through modification treatment and ultrasonic dispersion. The intermittent pulse electric field is applied during the resin precuring stage, and the filler is arranged in a directional manner to build an efficient thermal conductivity network.

Benefits of technology

It significantly improves the thermal conductivity and wear resistance of the silicone composite resin, enhances the filler-matrix interface strength, delays crack propagation, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912815A_ABST
    Figure CN119912815A_ABST
Patent Text Reader

Abstract

The invention provides heat-conducting wear-resistant organic silicon composite resin and a preparation method thereof, and belongs to the technical field of organic silicon preparation. The preparation process comprises the following steps: preparing the dual-modified boron nitride nanosheet; preparing a MoS < 2 > / NiPS hybrid body; silicon dioxide modification treatment; and preparing the organic silicon composite resin. The modified nano silicon dioxide, the MoS2-coated NiPS hybrid and the double-modified boron nitride nanosheets are added, and triple optimization of multi-shape filler cooperation, coupling agent modification and electric field arrangement is carried out, so that the heat-conducting property and the wear resistance of the organic silicon resin can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organosilicon preparation, and in particular to a heat-conductive and wear-resistant organosilicon composite resin and a preparation method thereof. Background Art

[0002] In the process of rapid development of modern industry and technology, silicone resin has been widely used in many fields due to its excellent properties, such as excellent weather resistance, good electrical insulation and high chemical stability. For example, it is used as electronic packaging materials in the electronic and electrical industry to effectively protect the internal precision electronic components; it is used as coatings for aircraft in the aerospace field to resist the erosion of harsh environments; and it is also used as sealing materials in automobile manufacturing to ensure the normal operation of components.

[0003] However, as various industries continue to move towards high performance and high reliability, the shortcomings of traditional silicone resins in thermal conductivity and wear resistance have gradually become prominent, becoming a key factor limiting its further expansion of application scope.

[0004] In terms of thermal conductivity, high-power electronic devices such as 5G base station chips and high-performance computer CPUs will generate a lot of heat during operation. If the heat is not dissipated in time, the device temperature will be too high, which will lead to performance degradation, shortened life and even failure. The thermal conductivity of traditional silicone resins is usually at a low level, which is difficult to meet the needs of fast and efficient heat dissipation in such high heat flux density scenarios. Although past studies have tried to add various types of thermally conductive fillers, such as metal oxides, to improve the thermal conductivity of silicone resins, these high thermal conductivity fillers are very easy to agglomerate in the silicone resin matrix, making it impossible to effectively construct the thermal conductive path and fail to significantly improve the thermal conductivity.

[0005] Wear resistance is also an important factor restricting the application of silicone resin. In the fields of machinery manufacturing, automotive parts, etc., there are many parts that need to withstand frequent friction and wear, such as engine piston seals, gear transmission parts, etc. Due to the molecular structure characteristics of silicone resin, the molecular chain is prone to breakage and slippage during long-term friction, resulting in severe wear on the material surface, affecting the normal service life and working accuracy of the parts. Although wear resistance has been improved by adding hard ceramic particles (such as SiC) and fibers (such as carbon fiber), the interface compatibility between these additives and the silicone resin matrix is ​​poor, and they are prone to fall off during friction, which accelerates the wear of the material.

[0006] It can be seen that developing a method that can effectively improve thermal conductivity and wear resistance has become an important issue that needs to be urgently solved in the current related fields. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a thermally conductive and wear-resistant organic silicon composite resin and a preparation method thereof.

[0008] A method for preparing a heat-conductive and wear-resistant organic silicon composite resin comprises the following steps: S1: Preparation of doubly modified boron nitride nanosheets Firstly, sodium hydride and tetrahydrofuran are mixed and then a castor oil-tetrahydrofuran mixed solution is added dropwise to prepare sodium ricinoleate, and then the boron nitride nanosheets are modified by sodium ricinoleate and then the boron nitride nanosheets are modified by dopamine to prepare double-modified boron nitride nanosheets; S2: Preparation of MoS2@NiPS hybrid MoS2 powder was first mixed with n-butyl lithium solution diluted with n-hexane for reaction, then mixed with γ-aminopropyltriethoxysilane and ethanol, and finally nickel chloride hexahydrate, ethanol and NaOH solution were added to react to prepare MoS2@NiPS hybrid; S3: Silica modification treatment Using silane coupling agent to modify silicon dioxide; S4: Preparation of silicone composite resin The methylphenyl silicone resin was mixed with xylene solvent, and then modified nano-silica, MoS2@NiPS hybrid, double-modified boron nitride nanosheets and platinum catalyst were added, followed by pre-curing and curing, and an intermittent pulsed electric field was applied during the pre-curing stage to prepare a silicone composite resin.

[0009] Furthermore, step S1: preparation of double-modified boron nitride nanosheets specifically comprises the following steps: S1.1: After mixing 3-5 parts by weight of sodium hydride and 5-8 parts by weight of tetrahydrofuran, keep stirring under nitrogen protection for 20-30 minutes, then add a mixed solution of castor oil and tetrahydrofuran in a mass ratio of 1:2-3 through a constant pressure dropping funnel at 1-2 drops / s under nitrogen protection for 80-90 minutes. After the addition is complete, heat to 60-63°C, continue stirring and react for 4-6 hours, cool the reaction solution, centrifuge and evaporate to obtain sodium ricinoleate; S1.2: Add 3-5 parts by weight of sodium ricinoleate to 10-12 parts by weight of a 95:5 v / v mixture of anhydrous ethanol and deionized water, stir at 50-60°C for 30-40 min, then add 5-8 parts by weight of boron nitride nanosheets, continue stirring for 2-3 hours, and after the reaction is completed, wash with anhydrous ethanol 2-3 times, and then dry at 80-90°C for 16-19 hours to obtain the initially modified boron nitride nanosheets; S1.3: adding 2-3 parts by weight of the preliminarily modified boron nitride nanosheets to 50-60 parts by weight of deionized water, and then ultrasonically dispersing at 200-300 W and 40-50 kHz for 20-30 min to obtain a suspension; S1.4: Dissolve 0.2-0.4 parts by weight of dopamine hydrochloride in 20-30 parts by weight of Tris buffer at pH 8.5 to obtain a dopamine solution, mix the suspension with the dopamine solution in a volume ratio of 1:1, and stir magnetically at 25-26°C for 24-30 hours, then centrifuge, wash, and dry to obtain double-modified boron nitride nanosheets.

[0010] Further, step S2: preparation of MoS2@NiPS hybrid specifically comprises the following steps: S2.1: Mix 2-3 parts by weight of MoS2 powder and 36-42 parts by weight of n-butyllithium solution and react in a reactor at 80-90°C for 4-5 hours. After cooling, filter, rinse with n-hexane, and dry to obtain Li x MoS2, wherein the n-butyl lithium solution is a n-butyl lithium solution diluted to a concentration of 0.5 M using n-hexane; S2.2: 1-2 parts by weight of Li x MoS2 is added to 200-230 parts by weight of deionized water, and then ultrasonically treated for 4-5 hours to obtain a suspension, 50-60 parts by weight of ethanol is added to 0.2-0.3 parts by weight of γ-aminopropyltriethoxysilane, stirred and mixed, and then added to the suspension, and stirred for 4-5 hours to obtain a mixed system; S2.3: Add 0.5-0.6 parts by weight of nickel chloride hexahydrate and 50-60 parts by weight of ethanol to the mixed system, and then add 11.1-11.2 parts by weight of 1M NaOH solution, continue stirring for 20-30 minutes, stop stirring and let stand for 3-4 minutes, then age for 72-78 hours, and obtain MoS2@NiPS hybrid after centrifugation, drying and grinding.

[0011] Further, step S3: silicon dioxide modification treatment, specifically comprises the following steps: S3.1: Add 1-2 parts by weight of nano-silicon dioxide to 30-40 parts by weight of anhydrous ethanol, stir and mix for 20-30 minutes at room temperature to obtain a silicon dioxide dispersion, add 5-8 parts by weight of silane coupling agent KH550 to 10-18 parts by weight of deionized water, and then stir and mix for 20-30 minutes to obtain a silane coupling agent mixed solution; S3.2: After mixing the silane coupling agent mixed liquid and the silica dispersion liquid, stir and mix at 400-500r / min for 1-2h, then condense and reflux for 3-4h at 70-72℃. After the reaction, wash with anhydrous ethanol, filter and vacuum dry to obtain modified nano-silica.

[0012] Furthermore, step S4: preparation of the organosilicon composite resin specifically comprises the following steps: S4.1: Mix methylphenyl silicone resin and xylene solvent in a mass ratio of 1:1, stir until completely dissolved to obtain a resin solution, then add modified nano-silica, MoS2@NiPS hybrid and double-modified boron nitride nanosheets to the resin solution, ultrasonically disperse for 20-30 minutes, and then stir at 2000-3000 rpm for 20-30 minutes to obtain a mixture; S4.2: Add 0.05-0.3wt% platinum catalyst to the mixture and stir for 10-12 minutes to obtain slurry. Then pour the slurry into a mold and pre-cure it at 80-90℃ for 1-2h in a vacuum environment. Then cure it at 150-160℃ for 2-3h to obtain a silicone composite resin.

[0013] Furthermore, in step S4.1, the amount of modified nano-silica added is 5-10wt% of the resin solution, the amount of MoS2@NiPS hybrid added is 3-8wt% of the resin solution, and the amount of double-modified boron nitride nanosheets added is 10-15wt% of the resin solution.

[0014] Furthermore, in step S4.2, during the resin pre-curing stage, intermittent pulses are used to apply a pulsed electric field, which is turned on for 30-40 seconds and turned off for 5-10 seconds. The voltage amplitude is 5-8 kV, the frequency is 100-300 Hz, and the time is 1-2 hours.

[0015] A heat-conductive and wear-resistant organic silicon composite resin is prepared by any one of the methods for preparing a heat-conductive and wear-resistant organic silicon composite resin.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention uses castor oil to prepare a surface modifier sodium ricinoleate, uses sodium ricinoleate to modify boron nitride nanosheets, and then uses dopamine hydrochloride to modify them. The prepared double-modified boron nitride nanosheets are added to silicone resin. Sodium ricinoleate improves the compatibility of boron nitride nanosheets and silicone resin, reduces agglomeration, and promotes uniform dispersion. The strong adhesion of polydopamine forms a flexible interface layer on the surface of the boron nitride nanosheets, and combines with the matrix through hydrogen bonds and covalent bonds to enhance the filler-matrix interface strength. The double modification prevents the nanosheets from falling off during friction, reduces stress concentration, and delays crack propagation, thereby improving wear resistance. The double-modified boron nitride nanosheets are more likely to form an orderly arrangement during processing, increase the phonon conduction path, and improve the in-plane thermal conductivity. The polydopamine coating acts as a "molecular bridge" to reduce the phonon scattering between the filler and the matrix through strong interface bonding, and further reduce the interface thermal resistance. The synergistic effect of the double modification can significantly improve the overall thermal conductivity of the composite material.

[0017] 2. In the present invention, by adding a MoS2 hybrid modified with NiPS, the layered structure and high intrinsic thermal conductivity of MoS2 can form a heat conduction channel in the resin matrix, and the modification of NiPS can optimize its dispersibility, reduce the interfacial thermal resistance, and promote the efficient transfer of heat. NiPS can be combined with MoS2 through chemical bonds, enhance the interfacial compatibility between the hybrid and the silicone resin, reduce phonon scattering, and thus improve the overall thermal conductivity. The layered structure of MoS2 can form a transfer film on the friction surface, significantly reducing the friction coefficient. After NiPS modification, MoS2 is prevented from falling off due to mechanical shearing, thereby extending the lubrication life. Therefore, the addition of the MoS2 hybrid modified with NiPS can effectively improve the thermal conductivity and wear resistance of silicone.

[0018] 3. The present invention adds coupling agent-modified silica to the preparation of silicone resin. The coupling agent-modified silica can be dispersed in boron nitride nanosheets and MoS2 hybrids modified with NiPS. The granular silica and flaky boron nitride nanosheets and MoS2@NiPS hybrids are interconnected to form a heat conduction path. Compared with thermal conductive fillers of a single shape, mixing thermal conductive fillers of different shapes increases the possibility of mutual contact between fillers, which makes the constructed thermal conductive network more continuous. The in-plane heat transfer of the flaky filler and the point-to-surface connection of the granular filler work together to construct a three-dimensional network, effectively improving the thermal conductivity. The added coupling agent-modified silica can be combined with the surface of the boron nitride nanosheets and MoS2@NiPS hybrids. After the coupling agent is modified, the silica and the resin interface are more tightly bonded, thereby enhancing the overall structural stability and also improving the wear resistance of the silicone.

[0019] 4. The present invention applies an intermittent pulse electric field during the resin pre-curing stage. The pulse electric field orients the polar conductive filler along the direction of the electric field. The oriented flaky filler forms a continuous channel parallel to the direction of heat flow, and the in-plane thermal conductivity advantage is maximized. The electric field can break the random distribution of the filler, reconstruct a more efficient thermal conductive network, and reduce the gaps and dislocations between the fillers. The thermal conductivity of the silicone resin can be effectively improved through the triple optimization of multi-shape filler synergy, coupling agent modification and electric field arrangement. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.

[0021] Figure 1 The present invention is a flow chart of a method for preparing a heat-conductive and wear-resistant organic silicon composite resin used in an embodiment of the present invention.

[0022] Figure 2 Schematic diagram of the MoS2@NiPS hybrid reaction of the present invention. DETAILED DESCRIPTION

[0023] The following is a detailed description of a heat-conductive and wear-resistant organic silicon composite resin and a preparation method thereof provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0024] Sodium ricinoleate structure:

[0025] Example 1 A method for preparing a heat-conductive and wear-resistant organic silicon composite resin, such as Figure 1-Figure 2 As shown, the following steps are included: S1: Preparation of doubly modified boron nitride nanosheets S1.1: Mix 3 parts by weight of sodium hydride and 5 parts by weight of tetrahydrofuran, keep stirring under nitrogen protection for 20 minutes, then add a mixed solution of castor oil and tetrahydrofuran in a mass ratio of 1:2 through a constant pressure dropping funnel at 1 drop / s under nitrogen protection for 80 minutes. After the addition is complete, heat to 60°C, continue stirring and react for 4 hours, cool the reaction solution, centrifuge and evaporate to obtain sodium ricinoleate; S1.2: Add 3 parts by weight of sodium ricinoleate to 10 parts by weight of a 95:5 v / v mixture of anhydrous ethanol and deionized water, stir at 50°C for 30 min, then add 5 parts by weight of boron nitride nanosheets, continue stirring for 2 h, and after the reaction is completed, wash twice with anhydrous ethanol, and then dry at 80°C for 16 h to obtain the initially modified boron nitride nanosheets; S1.3: adding 2 parts by weight of the preliminarily modified boron nitride nanosheets to 50 parts by weight of deionized water, and then ultrasonically dispersing at 200 W and 40 kHz for 20 min to obtain a suspension; S1.4: 0.2 parts by weight of dopamine hydrochloride is dissolved in 20 parts by weight of a Tris buffer having a pH of 8.5 to obtain a dopamine solution, the suspension is mixed with the dopamine solution in a volume ratio of 1:1, and the mixture is magnetically stirred at 25°C for 24 hours, followed by centrifugation, washing, and drying to obtain a double-modified boron nitride nanosheet; S2: Preparation of MoS2@NiPS hybrid S2.1: 2 parts by weight of MoS2 powder and 36 parts by weight of n-butyl lithium solution were mixed and reacted in a reactor at 80°C for 4 hours. After cooling, the mixture was filtered, rinsed with n-hexane, and dried to obtain Li x MoS2, wherein the n-butyl lithium solution is a n-butyl lithium solution diluted to a concentration of 0.5 M using n-hexane; S2.2: 1 part by weight of Li x MoS2 was added to 200 parts by weight of deionized water, and then ultrasonically treated for 4 hours to obtain a suspension, 50 parts by weight of ethanol was added to 0.2 parts by weight of γ-aminopropyltriethoxysilane, stirred and mixed, and then added to the suspension, and stirred for 4 hours to obtain a mixed system; S2.3: 0.5 parts by weight of nickel chloride hexahydrate and 50 parts by weight of ethanol were added to the mixed system, followed by the addition of 11.1 parts by weight of a 1M NaOH solution, followed by continuous stirring for 20 minutes, followed by standing for 3 minutes after stopping stirring, followed by aging for 72 hours, and then obtaining a MoS2@NiPS hybrid after centrifugation, drying and grinding; S3: Silica modification treatment S3.1: 1 part by weight of nano-silicon dioxide is added to 30 parts by weight of anhydrous ethanol, and the mixture is stirred and mixed for 20 minutes at room temperature to obtain a silicon dioxide dispersion liquid; 5 parts by weight of silane coupling agent KH550 is added to 10 parts by weight of deionized water, and the mixture is stirred and mixed for 20 minutes to obtain a silane coupling agent mixed liquid; S3.2: After mixing the silane coupling agent mixed liquid and the silica dispersion liquid, stir and mix at 400 r / min for 1 hour, then condense and reflux at 70° C. for 3 hours. After the reaction is completed, wash with anhydrous ethanol, filter, and vacuum dry to obtain modified nano-silica; S4: Preparation of silicone composite resin S4.1: Mix methylphenyl silicone resin and xylene solvent in a mass ratio of 1:1, stir until completely dissolved to obtain a resin solution, then add modified nano-silica, MoS2@NiPS hybrid and double-modified boron nitride nanosheets into the resin solution, ultrasonically disperse for 20 minutes, and then stir at 2000 rpm for 20 minutes to obtain a mixture; The amount of modified nano-silica added was 5wt% of the resin solution, the amount of MoS2@NiPS hybrid added was 3wt% of the resin solution, and the amount of double-modified boron nitride nanosheets added was 10wt% of the resin solution; S4.2: Add 0.05 wt% of platinum catalyst to the mixture, stir for 10 min to obtain slurry, then pour the slurry into a mold, pre-cure at 80° C. for 1 h under vacuum, and then cure at 150° C. for 2 h to obtain a silicone composite resin; In the resin pre-curing stage, intermittent pulses were used to apply a pulsed electric field, which was turned on for 30 seconds and turned off for 5 seconds. The voltage amplitude was 5 kV, the frequency was 100 Hz, and the time was 1 hour.

[0026] Example 2 A method for preparing a heat-conductive and wear-resistant organic silicon composite resin, such as Figure 1-Figure 2 As shown, the following steps are included: S1: Preparation of doubly modified boron nitride nanosheets S1.1: Mix 5 parts by weight of sodium hydride and 8 parts by weight of tetrahydrofuran, keep stirring under nitrogen protection for 20 minutes, then add a mixed solution of castor oil and tetrahydrofuran in a mass ratio of 1:3 through a constant pressure dropping funnel at 2 drops / s under nitrogen protection for 80 minutes. After the addition is complete, heat to 60°C, continue stirring and react for 4 hours, cool the reaction solution, centrifuge and evaporate to obtain sodium ricinoleate; S1.2: Add 5 parts by weight of sodium ricinoleate to 12 parts by weight of a 95:5 v / v mixture of anhydrous ethanol and deionized water, stir at 50°C for 30 min, then add 5-8 parts by weight of boron nitride nanosheets, continue stirring for 2 h, and after the reaction is completed, wash twice with anhydrous ethanol, and then dry at 80°C for 16 h to obtain the initially modified boron nitride nanosheets; S1.3: 3 parts by weight of the preliminarily modified boron nitride nanosheets are added to 60 parts by weight of deionized water, and then ultrasonically dispersed at 200 W and 40 kHz for 20 min to obtain a suspension; S1.4: 0.4 parts by weight of dopamine hydrochloride is dissolved in 30 parts by weight of a pH 8.5 Tris buffer to obtain a dopamine solution, the suspension is mixed with the dopamine solution in a volume ratio of 1:1, and the mixture is magnetically stirred at 25°C for 24 hours, followed by centrifugation, washing, and drying to obtain a double-modified boron nitride nanosheet; S2: Preparation of MoS2@NiPS hybrid S2.1: 3 parts by weight of MoS2 powder and 42 parts by weight of n-butyl lithium solution were mixed and reacted in a reactor at 80°C for 4 hours. After cooling, the mixture was filtered, rinsed with n-hexane, and dried to obtain Li x MoS2, wherein the n-butyl lithium solution is a n-butyl lithium solution diluted to a concentration of 0.5 M using n-hexane; S2.2: 2 parts by weight of Li x MoS2 was added to 230 parts by weight of deionized water, and then ultrasonically treated for 4 hours to obtain a suspension, 60 parts by weight of ethanol was added to 0.3 parts by weight of γ-aminopropyltriethoxysilane, stirred and mixed, and then added to the suspension, and stirred for 4 hours to obtain a mixed system; S2.3: 0.6 parts by weight of nickel chloride hexahydrate and 60 parts by weight of ethanol were added to the mixed system, followed by the addition of 11.2 parts by weight of a 1M NaOH solution, followed by continuous stirring for 20 minutes, followed by standing for 3 minutes after stopping stirring, followed by aging for 72 hours, and then obtaining a MoS2@NiPS hybrid after centrifugation, drying and grinding; S3: Silica modification S3.1: 2 parts by weight of nano-silicon dioxide is added to 40 parts by weight of anhydrous ethanol, and the mixture is stirred and mixed at room temperature for 20 minutes to obtain a silicon dioxide dispersion liquid, and 8 parts by weight of a silane coupling agent KH550 is added to 18 parts by weight of deionized water, and the mixture is stirred and mixed for 20 minutes to obtain a silane coupling agent mixed liquid; S3.2: After mixing the silane coupling agent mixed liquid and the silica dispersion liquid, stir and mix at 400 r / min for 1 hour, then condense and reflux at 70° C. for 3 hours. After the reaction is completed, wash with anhydrous ethanol, filter, and vacuum dry to obtain modified nano-silica; S4: Preparation of silicone composite resin S4.1: Mix methylphenyl silicone resin and xylene solvent in a mass ratio of 1:1, stir until completely dissolved to obtain a resin solution, then add modified nano-silica, MoS2@NiPS hybrid and double-modified boron nitride nanosheets into the resin solution, ultrasonically disperse for 20 minutes, and then stir at 2000 rpm for 20 minutes to obtain a mixture; The amount of modified nano-silica added was 10wt% of the resin solution, the amount of MoS2@NiPS hybrid added was 8wt% of the resin solution, and the amount of double-modified boron nitride nanosheets added was 15wt% of the resin solution; S4.2: Add 0.3 wt % of platinum catalyst to the mixture, stir for 10 min to obtain slurry, then pour the slurry into a mold, pre-cure at 80° C. for 1 h under vacuum, and then cure at 150° C. for 2 h to obtain a silicone composite resin; In the resin pre-curing stage, intermittent pulses were used to apply a pulsed electric field, which was turned on for 30 seconds and turned off for 5 seconds. The voltage amplitude was 5 kV, the frequency was 100 Hz, and the time was 1 hour.

[0027] Example 3 A method for preparing a heat-conductive and wear-resistant organic silicon composite resin, such as Figure 1-Figure 2 As shown, the following steps are included: S1: Preparation of doubly modified boron nitride nanosheets S1.1: After mixing 3 parts by weight of sodium hydride and 8 parts by weight of tetrahydrofuran, keep stirring under nitrogen protection for 30 minutes, then add a mixed solution of castor oil and tetrahydrofuran in a mass ratio of 1:2 through a constant pressure dropping funnel at 1 drop / s under nitrogen protection for 90 minutes. After the addition is completed, the temperature is raised to 63°C, and the reaction is continued with stirring for 6 hours. After cooling, the reaction solution is centrifuged and evaporated to obtain sodium ricinoleate; S1.2: Add 3 parts by weight of sodium ricinoleate to 10 parts by weight of a 95:5 v / v mixture of anhydrous ethanol and deionized water, stir at 60°C for 40 min, then add 5 parts by weight of boron nitride nanosheets, continue stirring for 3 h, and after the reaction is completed, wash with anhydrous ethanol 3 times, and then dry at 90°C for 19 h to obtain the initially modified boron nitride nanosheets; S1.3: 2 parts by weight of the preliminarily modified boron nitride nanosheets were added to 50 parts by weight of deionized water, and then ultrasonically dispersed at 300 W and 50 kHz for 30 min to obtain a suspension; S1.4: 0.2 parts by weight of dopamine hydrochloride is dissolved in 20 parts by weight of a Tris buffer having a pH of 8.5 to obtain a dopamine solution, the suspension is mixed with the dopamine solution in a volume ratio of 1:1, and the mixture is magnetically stirred at 26°C for 30 hours, followed by centrifugation, washing, and drying to obtain a double-modified boron nitride nanosheet; S2: Preparation of MoS2@NiPS hybrid S2.1: 2 parts by weight of MoS2 powder and 36 parts by weight of n-butyllithium solution were mixed and reacted in a reactor at 90°C for 5 hours. After cooling, the mixture was filtered, rinsed with n-hexane, and dried to obtain Li xMoS2, wherein the n-butyl lithium solution is a n-butyl lithium solution diluted to a concentration of 0.5 M using n-hexane; S2.2: 1 part by weight of Li x MoS2 was added to 200 parts by weight of deionized water, and then ultrasonically treated for 5 hours to obtain a suspension, 50 parts by weight of ethanol was added to 0.2 parts by weight of γ-aminopropyltriethoxysilane, stirred and mixed, and then added to the suspension, and stirred for 5 hours to obtain a mixed system; S2.3: 0.5 parts by weight of nickel chloride hexahydrate and 50 parts by weight of ethanol were added to the mixed system, followed by 11.1 parts by weight of a 1M NaOH solution, and the mixture was stirred for 30 minutes. After the stirring was stopped, the mixture was allowed to stand for 4 minutes, and then aged for 8 hours. After centrifugation, drying and grinding, the MoS2@NiPS hybrid was obtained. S3: Silica modification treatment S3.1: 1 part by weight of nano-silicon dioxide is added to 30 parts by weight of anhydrous ethanol, and the mixture is stirred and mixed for 30 minutes at room temperature to obtain a silicon dioxide dispersion liquid; 5 parts by weight of silane coupling agent KH550 is added to 10 parts by weight of deionized water, and the mixture is stirred and mixed for 30 minutes to obtain a silane coupling agent mixed liquid; S3.2: After mixing the silane coupling agent mixed liquid and the silica dispersion liquid, stir and mix at 500 r / min for 2 hours, then condense and reflux at 72° C. for 4 hours, wash with anhydrous ethanol after the reaction, filter and vacuum dry to obtain modified nano-silica; S4: Preparation of silicone composite resin S4.1: Mix methylphenyl silicone resin and xylene solvent in a mass ratio of 1:1, stir until completely dissolved to obtain a resin solution, then add modified nano-silica, MoS2@NiPS hybrid and double-modified boron nitride nanosheets to the resin solution, ultrasonically disperse for 30 minutes, and then stir at 3000 rpm for 30 minutes to obtain a mixture; The amount of modified nano-silica added was 5wt% of the resin solution, the amount of MoS2@NiPS hybrid added was 3wt% of the resin solution, and the amount of double-modified boron nitride nanosheets added was 10wt% of the resin solution; S4.2: Add 0.05 wt% of platinum catalyst to the mixture, stir for 12 minutes to obtain slurry, then pour the slurry into a mold, pre-cure at 90° C. for 2 hours under vacuum environment, and then cure at 160° C. for 3 hours to obtain a silicone composite resin; During the resin pre-curing stage, intermittent pulses were used to apply a pulsed electric field, which was turned on for 40 seconds and turned off for 10 seconds. The voltage amplitude was 8 kV, the frequency was 300 Hz, and the time was 2 hours.

[0028] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes steps S1.1-S1.2, replaces the initially modified boron nitride nanosheets in step S1.3 with boron nitride nanosheets, and prepares the organosilicon composite resin without changing the other steps, which is recorded as Comparative Example 1.

[0029] Comparative Example 2 Compared with Example 1, the difference of Comparative Example 2 is that Comparative Example 2 removes steps S1.3-S1.4, replaces the doubly modified boron nitride nanosheets in step S4.1 with the preliminarily modified boron nitride nanosheets, and prepares the organosilicon composite resin without changing the other steps, which is recorded as Comparative Example 2.

[0030] Comparative Example 3 Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes step S1, replaces the doubly modified boron nitride nanosheets in S4.1 with boron nitride nanosheets, and prepares the organosilicon composite resin without changing the other steps, which is recorded as Comparative Example 3.

[0031] Comparative Example 4 Compared with Example 1, the difference of Comparative Example 4 is that the MoS2@NiPS hybrid in steps S2 and S4.1 is removed in Comparative Example 4, and the remaining steps remain unchanged to prepare the organosilicon composite resin, which is recorded as Comparative Example 4.

[0032] Comparative Example 5 Compared with Example 1, the difference of Comparative Example 5 is that Comparative Example 5 removes step S2, replaces the MoS2@NiPS hybrid in S4.1 with a mixture of MoS2 and NiPS, and prepares the organosilicon composite resin without changing the other steps, which is recorded as Comparative Example 5.

[0033] Comparative Example 6 Compared with Example 1, the difference of Comparative Example 6 is that, in Comparative Example 6, the modified nano-silica in steps S3 and S4.1 is removed, and the remaining steps remain unchanged to prepare the organosilicon composite resin, which is recorded as Comparative Example 6.

[0034] Comparative Example 7 Compared with Example 1, the difference of Comparative Example 7 is that the intermittent pulse electric field in step S4.2 is removed in Comparative Example 7, and the other steps are unchanged to prepare the organosilicon composite resin, which is recorded as Comparative Example 7.

[0035] The silicone composite resins prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to a wear resistance test. The wear resistance was measured according to the Ford FLTM-BN-108-13 scratch resistance standard. The test was performed using a wear tester. All scratches were checked according to the grade rating, where grade 1 was the best (no scratches) and grade 5 was the worst (severe scratches). The test results are shown in Table 1.

[0036] Table 1. Wear test results of silicone composite resin

[0037] From the data of Table 1 and Comparative Examples 1-3, it can be seen that the double-modified boron nitride nanosheets can improve the wear resistance compared with the single modification. From the data of Comparative Examples 4 and 5, it can be seen that the MoS2 hybrid modified with NiPS has a better effect on improving the wear resistance than the simple physical mixing. From the data of Comparative Example 6, it can be seen that the addition of modified silica effectively improves the wear resistance of the silicone resin.

[0038] The thermal conductivity of the organosilicon composite resins prepared in Examples 1-3 and Comparative Examples 1-7 was tested. The test results are shown in Table 2.

[0039] Table 2. Thermal conductivity test results of silicone composite resin

[0040] From Table 2, it can be seen from the data of Comparative Examples 1-3 that the doubly modified boron nitride nanosheets can significantly improve the overall thermal conductivity of the composite material. From the data of Comparative Examples 4-5, it can be seen that the addition of MoS2 hybrid modified with NiPS can effectively improve the thermal conductivity of silicone, while simple physical mixing reduces the thermal conductivity of silicone. From the data of Comparative Example 6, it can be seen that adding silica modified by coupling agent to the preparation of silicone resin can effectively improve the thermal conductivity. From the data of Comparative Example 7, it can be seen that applying an intermittent pulsed electric field can effectively improve the thermal conductivity of silicone resin.

[0041] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a heat-conductive and wear-resistant organic silicon composite resin, characterized in that: The steps include: S1: Preparation of doubly modified boron nitride nanosheets Firstly, sodium hydride and tetrahydrofuran are mixed and then a castor oil-tetrahydrofuran mixed solution is added dropwise to prepare sodium ricinoleate, and then the boron nitride nanosheets are modified by sodium ricinoleate and then the boron nitride nanosheets are modified by dopamine to prepare double-modified boron nitride nanosheets; S2: Preparation of MoS2@NiPS hybrid MoS2 powder was first mixed with n-butyl lithium solution diluted with n-hexane for reaction, then mixed with γ-aminopropyltriethoxysilane and ethanol, and finally nickel chloride hexahydrate, ethanol and NaOH solution were added to react to prepare MoS2@NiPS hybrid; S3: Silica modification The silicon dioxide is modified by using a silane coupling agent; S4: Preparation of silicone composite resin The methylphenyl silicone resin was mixed with xylene solvent, and then modified nano-silica, MoS2@NiPS hybrid, double-modified boron nitride nanosheets and platinum catalyst were added, followed by pre-curing and curing, and an intermittent pulsed electric field was applied during the pre-curing stage to prepare a silicone composite resin.

2. The method for preparing a heat-conductive and wear-resistant organic silicon composite resin according to claim 1, characterized in that: Step S1: Preparation of double-modified boron nitride nanosheets, specifically comprising the following steps: S1.1: After mixing 3-5 parts by weight of sodium hydride and 5-8 parts by weight of tetrahydrofuran, keep stirring under nitrogen protection for 20-30 minutes, then add a mixed solution of castor oil and tetrahydrofuran in a mass ratio of 1:2-3 through a constant pressure dropping funnel at 1-2 drops / s under nitrogen protection for 80-90 minutes. After the addition is complete, heat to 60-63°C, continue stirring and react for 4-6 hours, cool the reaction solution, centrifuge and evaporate to obtain sodium ricinoleate; S1.2: Add 3-5 parts by weight of sodium ricinoleate to 10-12 parts by weight of a 95:5 v / v mixture of anhydrous ethanol and deionized water, stir at 50-60°C for 30-40 min, then add 5-8 parts by weight of boron nitride nanosheets, continue stirring for 2-3 hours, and after the reaction is completed, wash with anhydrous ethanol 2-3 times, and then dry at 80-90°C for 16-19 hours to obtain the initially modified boron nitride nanosheets; S1.3: adding 2-3 parts by weight of the preliminarily modified boron nitride nanosheets to 50-60 parts by weight of deionized water, and then ultrasonically dispersing at 200-300 W and 40-50 kHz for 20-30 min to obtain a suspension; S1.4: Dissolve 0.2-0.4 parts by weight of dopamine hydrochloride in 20-30 parts by weight of Tris buffer at pH 8.5 to obtain a dopamine solution, mix the suspension with the dopamine solution in a volume ratio of 1:1, and stir magnetically at 25-26°C for 24-30 hours, then centrifuge, wash, and dry to obtain double-modified boron nitride nanosheets.

3. The method for preparing a heat-conductive and wear-resistant organic silicon composite resin according to claim 2, characterized in that: Step S2: Preparation of MoS2@NiPS hybrid, specifically comprising the following steps: S2.1: Mix 2-3 parts by weight of MoS2 powder and 36-42 parts by weight of n-butyllithium solution and react in a reactor at 80-90°C for 4-5 hours. After cooling, filter, rinse with n-hexane, and dry to obtain Li x MoS2, wherein the n-butyl lithium solution is a n-butyl lithium solution diluted to a concentration of 0.5 M using n-hexane; S2.2: 1-2 parts by weight of Li x MoS2 is added to 200-230 parts by weight of deionized water, and then ultrasonically treated for 4-5 hours to obtain a suspension, 50-60 parts by weight of ethanol is added to 0.2-0.3 parts by weight of γ-aminopropyltriethoxysilane, stirred and mixed, and then added to the suspension, and stirred for 4-5 hours to obtain a mixed system; S2.3: Add 0.5-0.6 parts by weight of nickel chloride hexahydrate and 50-60 parts by weight of ethanol to the mixed system, and then add 11.1-11.2 parts by weight of 1M NaOH solution, continue stirring for 20-30 minutes, stop stirring and let stand for 3-4 minutes, then age for 72-78 hours, and obtain MoS2@NiPS hybrid after centrifugation, drying and grinding.

4. The method for preparing a heat-conductive and wear-resistant organic silicon composite resin according to claim 3, characterized in that: Step S3: silicon dioxide modification treatment, specifically comprising the following steps: S3.1: Add 1-2 parts by weight of nano-silicon dioxide to 30-40 parts by weight of anhydrous ethanol, stir and mix for 20-30 minutes at room temperature to obtain a silicon dioxide dispersion, add 5-8 parts by weight of silane coupling agent KH550 to 10-18 parts by weight of deionized water, and then stir and mix for 20-30 minutes to obtain a silane coupling agent mixed solution; S3.2: After mixing the silane coupling agent mixed liquid and the silica dispersion liquid, stir and mix at 400-500r / min for 1-2h, then condense and reflux for 3-4h at 70-72℃. After the reaction, wash with anhydrous ethanol, filter and vacuum dry to obtain modified nano-silica.

5. The method for preparing a heat-conductive and wear-resistant organic silicon composite resin according to claim 4, characterized in that: Step S4: Preparation of organic silicon composite resin, specifically comprising the following steps: S4.1: Mix methylphenyl silicone resin and xylene solvent in a mass ratio of 1:1, stir until completely dissolved to obtain a resin solution, then add modified nano-silica, MoS2@NiPS hybrid and double-modified boron nitride nanosheets to the resin solution, ultrasonically disperse for 20-30 minutes, and then stir at 2000-3000 rpm for 20-30 minutes to obtain a mixture; S4.2: Add 0.05-0.3wt% platinum catalyst to the mixture and stir for 10-12 minutes to obtain slurry. Then pour the slurry into a mold and pre-cure it at 80-90℃ for 1-2h in a vacuum environment. Then cure it at 150-160℃ for 2-3h to obtain a silicone composite resin.

6. The method for preparing a heat-conductive and wear-resistant organic silicon composite resin according to claim 5, characterized in that: In step S4.1, the amount of modified nano-silica added is 5-10wt% of the resin solution, the amount of MoS2@NiPS hybrid added is 3-8wt% of the resin solution, and the amount of double-modified boron nitride nanosheets added is 10-15wt% of the resin solution.

7. The method for preparing a heat-conductive and wear-resistant organic silicon composite resin according to claim 5, characterized in that: In step S4.2, during the resin pre-curing stage, intermittent pulses are used to apply a pulsed electric field, which is turned on for 30-40 seconds and turned off for 5-10 seconds. The voltage amplitude is 5-8 kV, the frequency is 100-300 Hz, and the time is 1-2 hours.

8. A thermally conductive and wear-resistant organic silicon composite resin, characterized in that: The thermally conductive and wear-resistant organic silicon composite resin is prepared by the method for preparing the thermally conductive and wear-resistant organic silicon composite resin according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of BN / epoxy resin heat conductive insulation composite material

    CN109280332A

  • Preparation method of high-thermal-conductivity three-phase composite film under assistance of electric field

    CN113416332A

  • Preparation method and application of pulsed electric field induced high-thermal-conductivity epoxy composite material

    CN119490684A

  • Modified boron nitride, composite material containing same, preparation method therefor, and application thereof

    WO2023274068A1